40Ar/39Ar Geochronology of Volcanic and Intrusive Rocks in the Papandayan Metallic Prospect Area, West Java, Indonesia. Issue 1 (January 2017) - Titisari, Anastasia Dewi; Phillips, David; Prayatna,; Setyaraharja, Eko Purwanto
Abstract: This study presents new 40 Ar/ 39 Ar ages on the volcanic and intrusive rocks from the Papandayan metallic district in West Java, Indonesia. The vein system in the Arinem area, one of the prospective areas in the district, has been considered as an epithermal gold–silver–base metal deposit, however, no published age results are available for the host volcanic rocks in the district. The ages of these rocks are critical in terms of their association with mineralization and are important to understand the evolution of volcanism in the region, which has implications for mineral exploration in the district. 40 Ar/ 39 Ar plateau ages of two typical basalt and one andesite samples of the Jampang Formation volcanic rocks yielded ages of 11.65 ± 0.52 Ma, 18.15 ± 0.46 Ma and 7.69 ± 0.05 Ma, respectively. 40 Ar/ 39 Ar ages of three intrusive rock samples from Gunung Halang diorite, Gunung Lingga diorite, and Gunung Buligir fine‐grained quartz diorite yielded ages of 12.98 ± 0.20 Ma, 10.81 ± 0.15 Ma, and 7.37 ± 0.05 Ma, respectively. The age of the youngest fine‐grained diorite (Gunung Wayang dike) is 3.95 ± 0.03 Ma. An 40 Ar/ 39 Ar age obtained from adularia in the Arinem mineralized vein (18.30 ± 0.20 Ma) is older than the age of altered basalt sample of this study (11.65 ± 0.52 Ma) and the K–Ar illite ages of the Arinem vein (9.4 ± 0.3 Ma and 8.8 ± 0.3 Ma) which resulted from a previous study. The age results suggest that the Papandayan district may have experienced multiple hydrothermal and mineralization events. This study, therefore, provides crucial age data to support future mineral exploration in the district. Abstract : This study presents new 40Ar/39Ar ages on the volcanic and intrusive rocks from the Papandayan metallic district in West Java, Indonesia. The ages of these rocks are critical in terms of their association with mineralization and are important to understand the evolution of volcanism in the region. The age results suggest that the Papandayan district may have experienced multiple hydrothermal and mineralization events. This study, therefore, provides crucial age data to support future mineral exploration in the district.